Observational constraint on cloud susceptibility weakened by aerosol retrieval limitations - Po-Lun Ma; Philip J. Rasch; Hélène Chepfer; David M. Winker; Steven J. Ghan (Nature Communications, 2018)
Cloud susceptibility to aerosols in models frequently exceeds satellite estimates. Here the authors show that the discrepancy can be explained by retrieval limitations especially in clean environments, suggesting that conventional comparison strategies may lead to misunderstanding.